Inferring agent behavior and economic information, with free entry and exit of firms (2011)
This article proposes an identity regarding economic outcomes when producers maximize profits, with free entry and exit of firms. The identity links consumer and producer theory and leads to several results that contribute to understand what should -and should not- be expected under the assumptions made, from the behavior of firms and households, and from the technology of a firm. Given that unit prices are usually known, the identity also allows to infer the value of a range of economic variables, when reasonable information is available on the price elasticity of the residual demand, the marginal revenue associated to the residual demand, the marginal cost or the elasticity of scale.